Early Childhood Symbolic Thinking Skills through Loose Part-Based Busy Jar Learning Media - Mufida, Aina Yulifa'atun; Hibana, Hibana (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
Early childhood cognitive development is a very important and decisive phase. This ability refers to the ability of children to use certain symbols or representations to describe objects that are not in front of them. Through symbolic thinking skills, children can begin to develop the ability to think abstractly and imaginatively. This is an important foundation that will support their ability to think critically and creatively in the future. This research uses qualitative descriptive research. The subjects in this research were 23 children from KB Paud Aisyiah 02 Tambakromo. The data in this research was collected through several techniques, namely observation, interviews and documentation. The data obtained in this research was collected and analyzed using thematic analysis techniques with data analysis steps including Data Reduction, Data Presentation, and Conclusion Drawing.The result obtained is that symbolic thinking ability is one of the initial stages in the development of pre-operational thinking. At this stage, children begin to be able to mentally imagine an object even though the object is not present in front of them. Busy jar is a variety of children's games, which consists of jars (jars) that contain game materials and can be used as a means of learning for children. Through loose part-based busy jar learning media, it can help the development of symbolic abilities in early childhood.